2013
DOI: 10.1186/1756-3305-6-145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aedes aegypti exposure to spatial repellent chemicals on BG-Sentinel™ trap catches

Abstract: BackgroundAn integrated approach to reduce densities of adult Aedes aegypti inside homes is currently being evaluated under experimentally controlled field conditions. The strategy combines a spatial repellent (SR) treatment (applied indoors) with the Biogents Sentinel™ (BGS) mosquito trap positioned in the outdoor environment. In essence, when combined, the goal is to create a push-pull mechanism that will reduce the probability of human-vector contact. The current study measured BGS recapture rates of Ae. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
3
25
2
Order By: Relevance
“…aegypti females to pyrethroids did not significantly reduce the attraction of BGS traps. 64 This finding supports the potential effectiveness of a push-pull strategy to reduce Ae. aegypti adults inside and outside homes.…”
Section: Mechanical Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…aegypti females to pyrethroids did not significantly reduce the attraction of BGS traps. 64 This finding supports the potential effectiveness of a push-pull strategy to reduce Ae. aegypti adults inside and outside homes.…”
Section: Mechanical Methodssupporting
confidence: 54%
“…Semi‐field experiments showed that exposure of Ae. aegypti females to pyrethroids did not significantly reduce the attraction of BGS traps . This finding supports the potential effectiveness of a push‐pull strategy to reduce Ae.…”
Section: Mechanical Methodsmentioning
confidence: 99%
“…While this showed that trans uthrin did not actively push mosquitoes into the trap it also indicated that trans uthrin exposure outdoors does not inhibit mosquitoes entering the BGS. This is contrary to Salazar et al (2013) who reported that exposing mosquitoes to trans uthrin signi cantly lowered trap catches [38]. However, trap catches were not affected if the mosquitoes allowed to recover for 12 h before BGS trap evaluation [38].…”
Section: Discussionmentioning
confidence: 60%
“…This is contrary to Salazar et al (2013) who reported that exposing mosquitoes to trans uthrin signi cantly lowered trap catches [38]. However, trap catches were not affected if the mosquitoes allowed to recover for 12 h before BGS trap evaluation [38]. This suggests that the mode of action of trans uthrin is dose and distance dependent and repellency is reversible (i.e.…”
Section: Discussionmentioning
confidence: 62%
“…togoi (Theobald), Anopheles arabiensis (Giles), and Ae. aegypti . Meperfluthrin is a lesser known polyfluorinated pyrethroid, but was reported to have caused 97%, 97%, and 92% mortality when delivered through a mosquito coil against An.…”
Section: Introductionmentioning
confidence: 99%